2007
DOI: 10.1111/j.1600-6143.2007.02011.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantiferon-TB Gold With Tuberculin Skin Test for Detecting Latent Tuberculosis Infection Prior to Liver Transplantation

Abstract: Screening for latent tuberculosis infection (LTBI) is recommended prior to organ transplantation. TheQuantiferon-TB Gold assay (QFT-G) may be more accurate than the tuberculin skin test (TST) in the detection of LTBI. We prospectively compared the results of QFT-G to TST in patients with chronic liver disease awaiting transplantation. Patients were screened for LTBI with both the QFT-G test and a TST. Concordance between test results and predictors of a discordant result were determined. Of the 153 evaluable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
103
2
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 20 publications
15
103
2
3
Order By: Relevance
“…Interferon-gamma release assays have been tested and found to perform reasonably well in healthy populations as well as in patients with end-stage liver disease. [16][17][18][19] …”
Section: Diagnosis Of Tuberculosis In End-stage Liver Diseasementioning
confidence: 99%
“…Interferon-gamma release assays have been tested and found to perform reasonably well in healthy populations as well as in patients with end-stage liver disease. [16][17][18][19] …”
Section: Diagnosis Of Tuberculosis In End-stage Liver Diseasementioning
confidence: 99%
“…Concordance between the 2 tests was 85.1% (k ¼ 0.60), and this suggests that QFT was comparable to PPD for the diagnosis of latent TB in this population. 12 Another study comparing QFT to PPD testing in patients with chronic liver disease revealed fewer positive results with PPD testing. 13 Currently, there is no reported advantage for one test versus the other; but in normal hosts, interferon-c release assays have the advantage of differentiating people whose positive skin test reflects prior vaccination against Bacille Calmette-Guérin (BCG) infection.…”
Section: Diagnosis Latent Tbmentioning
confidence: 99%
“…[14][15][16] Because both QFT and TST measure the cellular immune response to M. tuberculosis, testing with QFT is unlikely to be helpful in patients with a negative TST related to defective cellular immune responses. 11,12 The full evaluation of a patient with cirrhosis before liver transplantation should be thorough and include a detailed medical and exposure history and a review of chest radiography (see the section on the evaluation of transplant candidates and donors). In posttransplant recipients, the diagnosis of LTBI similarly involves the use of TST or interferon-c release assay testing.…”
Section: Diagnosis Latent Tbmentioning
confidence: 99%
“…When screening recipients, the decrease in test sensitivity with increasing immunosuppression has important practical consequences, as screening should be carried out before administration of immunosuppressive drugs to ensure sensitivity and to allow sufficient time to initiate chemoprophylaxis. Studies in transplant candidates prior to liver [62,63] or renal transplantation indicate that IGRAs may be applied, although agreement between TST and IGRAs in renal transplant candidates is only fair to moderate [64][65][66][67][68].…”
Section: Risk Of Tb In Sot Recipientsmentioning
confidence: 99%
“…Whilst neither M. bovis BCG nor most environmental mycobacteria influence the result of IGRAs, data regarding their value in immunosuppressed children and young children are lacking. Studies evaluating IGRAs in transplant candidates to date have excluded children [62,63].…”
Section: Diagnosis Of Infection With M Tuberculosismentioning
confidence: 99%